Suku kata dasar dialek Kelantan berdasarkan teori Optimaliti - Abdul Aziz, Adi Yasran (Penerbit Universiti Kebangsaan Malaysia, 2011)
This paper describes the constraint interactions that account for the basic syllable types in the Kelantan Malay dialect based on Optimality Theory (OT). Previous analysis of basic syllables in Malay focused only on the possible types of syllables. These analyses do not offer any explanation on the differences found in the possible syllable types found in various Malay dialects even though they all originated from the same parent language. Most of these analyses described the basic syllable template as (consonant)-vowel- (consonant) or (C)V(C), CV, CVC, VC and V. Nevertheless, this paper presents an alternative description using a set of constraint hierarchy in the Kelantan grammar, which is different from the set of constraint hierarchy for the standard Malay variety, in order to account for the basic syllable types in Kelantan Malay. The set of constraints hierarchy proposed for Kelantan Malay comprises *COMPLEXNUCLEI, *COMPLEXCODA, CONTIGROOT >> ALIGN-LEFT >> ONSET >> DEP >> MAX >> *CODA. These constraints are considered universal in the human mind; however, its hierarchy depends on the constraints interaction of the language or the local dialect. The present analysis shows that the explanation available from constraints interaction from OT has greater explanatory power in describing the grammar of a language.